Sex differences in prevalence and risk factors of asymptomatic cholelithiasis in Korean health screening examinee: A retrospective analysis of a multicenter study. Issue 13 (March 2017) - Kim, Sung Bum; Kim, Kook Hyun; Kim, Tae Nyeun; Heo, Jun; Jung, Min Kyu; Cho, Chang Min; Lee, Yoon Suk; Cho, Kwang Bum; Lee, Dong Wook; Han, Ji Min; Kim, Ho Gak; Kim, Hyun Soo
Abstract : Abstract: The aim of this study was to evaluate sex difference in the prevalence and risk factors for asymptomatic cholelithiasis in Korean health screening examinees. Examinees who underwent examination through health promotion center at 5 hospitals of Daegu-Gyeongbuk province in 2014 were analyzed retrospectively. All examinees were checked for height, weight, waist circumference, and blood pressure, and underwent laboratory tests and abdominal ultrasound. Diagnosis of cholelithiasis was made by ultrasound. Of the total of 30, 544 examinees, mean age was 47.3 ± 10.9 years and male to female ratio was 1.4:1. Asymptomatic cholelithiasis was diagnosed in 1268 examinees with overall prevalence of 4.2%. In age below 40 years, females showed higher prevalence of asymptomatic cholelithiasis than males (2.7% vs. 1.9%, P  = 0.020), whereas prevalence of asymptomatic cholelithiasis was higher in males than females older than 50 years (6.2% vs. 5.1%, P  = 0.012). Multiple logistic regression analysis revealed age (≥50 years), obesity, and high blood pressure as risk factors for asymptomatic cholelithiasis in males and age, obesity, hypertriglyceridemia, and chronic hepatitis B infection in females ( P  < 0.05). Overall prevalence of asymptomatic cholelithiasis was 4.2% in Korean health screening examinees. Females showed higher prevalence of asymptomatic cholelithiasis than males younger than 40 years, whereas it was higher in males older than 50 years. Age and obesity were risk factors for asymptomatic cholelithiasis in both sexes. Males had additional risk factors of high blood pressure and females had hypertriglyceridemia and chronic hepatitis B infection.